Franz Hinkelammert. Formulación sistemática, crítica y original de filosofía marxista contemporánea: - Fernández Nadal, Estela (2022)
The work presents a synthesis of the main theoretical nuclei of Franz Hinkelammert’s philosophy. It emphasizes, on the one hand, its systematic character, observable in the internal articulation and coherence of the different disciplinary developments: anthropology, philosophy of history, ethics, politics, theology. On the other hand, it tries to show the fundamental reference of the whole to the thought of Karl Marx, a critical tradition within which Hinkelammert produces an original look. Regarding the systematic and totalizing nature of Hinkelammert’s reflection, the writing underlines the interweaving of his various contributions. In the field of philosophical anthropology, based on the central categories of intersubjectivity and infinity/finitude, the scope and limits of the subject are defined. The priority of the latter gives rise, in the field of the philosophy of history, to the critique of utopian reason. Ethics and politics appear as areas where the cry of the subject raises the demand for the common good and for a society in which everyone fits. Finally, the tour closes with a quick but eloquent outline of his political theology. In relation to the second aspect mentioned, the writing underlines the importance of Hinkelammert’s contribution to Marxism in two aspects. First, because it gives Marx’s thought a new validity, by reformulating it from a present dominated by globalization as a new matrix of capitalist accumulation. Second, because it discusses each point of Marx’s thought that, conditioned by its historical-social situation, raises doubts, outlines problematic answers or shows limits, making necessary, in Hinkelammert’s opinion, a review and update of his main ideas.